Analisis Qanun dan Perwujudan Syariat Islam pada Arsitektur Tradisonal Aceh: Studi Kasus: Rumoh Aceh - Hendra Fahruddin Siregar; Dara Wisdianti; Dewangga Futtra Yusnadi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2024)
Title: Analysis of Qanun and The Uniqueness of Regional Colors in Traditional Acehnese House Architecture Qanun are regulations related to Islamic Shari’a in aspects of life and society. The form of Islamic Shari’a in Aceh has been integrated into the form of architecture. This is stated in the form of traditional Rumoh Aceh culture, which closely relates to philosophy and Shari’a. The research aims to find out how much influence Qanun regulations have on the architecture of Rumoh Aceh and the typical colors used in it. This research uses descriptive and observational methods. The results of this research explain that Qanun regulations have a very close influence on the architecture of Rumoh Aceh. There are several things related to the shape of Rumoh Aceh, such as the shape of the building and the ornaments of the Aceh House, which are in the form of plants and other motifs and do not conflict with Islamic Shari’a. Apart from that, the color of Rumoh Aceh is very distinctive, with yellow dominating the meaning of health and warmth. These values are a cultural interpretation of the Acehnese people, which have been implemented for a long time as local wisdom, which is based on and in line with Qanun regulations.